ADAPTIVE ENVIRONMENTAL GOVERNANCE WITHIN A LEGAL PLURALISM FRAMEWORK: A Case Study of The Tengger Indigenous Community in Indonesia - Istislam Istislam; Iwan Permadi; Hezron Sabar Rotua Tinambunan; Pitoyo Widhi Atmoko; Cuikitalia Cuikitalia (Jurisdictie: Jurnal Hukum dan Syariah, 2026)
This article examines the gap between the constitutional recognition of Indigenous peoples’ rights and environmental governance practices in Indonesia. The study highlights the asymmetry between national environmental law and customary ecological governance within the Tengger community in the Bromo Tengger Semeru region of East Java. Its objective is to analyze the divergence between national law and customary law and to formulate an integrative model capable of bridging this gap. The study employs a socio-legal approach, combining normative legal analysis with empirical data obtained through in-depth interviews and focus group discussions conducted in Ngadas Village. The findings indicate that governance gaps arise not only from regulatory discrepancies but also from differing institutional perspectives. National law relies on administrative instruments, whereas Tengger customary law is grounded in moral-spiritual norms, collective rituals, and restorative sanctions. The study proposes the concept of Ecological Equilibrium Governance as an integrative framework that incorporates legal pluralism, adaptive governance, and principles of commons-based resource management. Its primary contribution lies in advancing Ecological Equilibrium Governance as a novel model that enriches environmental law scholarship while offering both normative and practical foundations for more inclusive and participatory policymaking. The study’s implications underscore the importance of institutional integration, adaptive co-management, and the strengthened participation of Indigenous communities. Artikel ini mengkaji kesenjangan antara pengakuan konstitusional atas hak-hak masyarakat adat dan praktik tata kelola lingkungan di Indonesia. Studi ini menyoroti asimetri antara hukum lingkungan nasional dan tata kelola ekologi berbasis adat di komunitas Tengger di wilayah Bromo Tengger Semeru, Jawa Timur. Tujuan studi ini adalah untuk menganalisis kesenjangan antara hukum nasional dan hukum adat serta merumuskan model integratif yang mampu menjembatani kesenjangan tersebut. Studi ini menggunakan penelitian sosio-legal, menggabungkan analisis hukum normatif dan data empiris melalui wawancara mendalam dan diskusi kelompok fokus di Desa Ngadas. Temuan menunjukkan bahwa kesenjangan tata kelola tidak hanya disebabkan oleh kesenjangan regulasi tetapi juga oleh perbedaan perspektif kelembagaan, dengan hukum nasional berbasis instrumen administratif, sementara hukum adat Tengger bergantung pada norma moral-spiritual, ritual kolektif, dan sanksi restoratif. Studi ini merekomendasikan konsep Ecological Equilibrium Governance sebagai kerangka kerja integratif yang menggabungkan pluralisme hukum, tata kelola adaptif, dan prinsip pengelolaan sumber daya bersama. Kontribusi utama penelitian ini adalah pengembangan konsep Ecological Equilibrium Governance sebagai model baru yang memperkaya studi hukum lingkungan dan menawarkan landasan normatif dan praktis untuk kebijakan yang lebih inklusif dan partisipatif. Implikasi penelitian menekankan integrasi kelembagaan, pengelolaan bersama yang adaptif, dan penguatan partisipasi masyarakat adat.